Computing steel frame analysis of behavior semi-rigid connection - Aco Wahyudi Efendi (International Journal of Advanced Science and Computer Applications, 2023)
Semi-rigid connections are very economical compared to other connections because they can prevent the frame from breaking immediately due to brittleness without endangering the entire structure. Steel frame construction is one of the types of construction described in the building codes for simple seismic buildings. The research on the use of this semi-rigid connection uses one of the computer software that uses the finite element method, namely ANSYS ED.9, by taking validation models from experimental and manual calculation analysis and using 35 research models with different loads, positions and number of bolts and types of portal bracing. The ability to survive on the gantry due to side loads is dominated by the number and position of the bolts and the type of gantry stiffener used, this is evident from the different models, with the rise ratio in each model ranging from 0.7852 to 2.5900 and in ranges of softening compared to clamped stiffeners, which experience a decrease in stress, with the same ratio.